REHABILITATION RESEARCH BARRIERS IN PAKISTAN - Unaiza Batool (The Rehabilitation Journal, 2018)
In diverse field of rehabilitation, it is so difficult for us to state that whether our work is debilitating or restorative. The impact of what we are doing is measured by the rehabilitation research. It is one of the source through which we test the belief of making a difference in the lives of people we serve.1 Major rehabilitation research barriers documented worldwide may include four major barriers: technical barriers-lack of access to library resources2, lack of familiarity with research process 3, 4, lack of research mentors5-7, and lack of statistical support8, personal barriers-lack of time4, social barriers-ethical concerns about use of human participants and animal subjects1 and professional barriers-lack of funds2 , clinician researcher dichotomy9. In Pakistan, the barriers in rehabilitation research correlate as lack of time (63%), lack of administrative support (38.9%), while 37% do research only for advancing in careers and 9.3% lack interest in research 10 . Another similar study showed 58% holding back in research due to limitation of time because of extensive curriculum 49.3% exam phobia and 16.7% lack of interest. Improper training in research methodology and scientific literature search were also documented to be two important barriers contributing 25.3% and 31.4% respectively 11. Limited access to the digital libraries impedes the know-how of the current and latest researches in the advancing, innovative field of rehabilitation. This barrier puts a restraint on gaining an insight in the area of interest hence proving to be a huge stone in doing quantitative as well as qualitative research work 12. The development and establishment of digital libraries is the direct after effect of lack of: concept of digital libraries, technological applications, and human resource with relevant skills, copyrights and financial support 13. Such barriers are a great hindrance in the quality of research work and negates rather than potentiation in narrowing of the gap between antiquated, still in practice techniques and modern modifications of regimen incarnated into the rehabilitation protocols. Due to the combination of lack of interest and pre-disposing factors, the rehabilitation research is in very critical phase. Moreover, if a research successfully goes through its final form by the experience, constant hard work, dedication and commitment, it still fails to appear on the larger grounds due to failure of publishing. This failure not only buries it under the heap of leaves but also result in continuation of the previously discarded techniques1. Research must be incorporated in undergraduate studies to properly produce trained students that will come forward and apprehend the challenges faced today. Independent learning, writing, and critical appraisal of the existing literature will become so easy by such assimilation of skills 14,15 . These skills also help in further postgraduate studies without wastage of further time in acquiring the research skills from a new and varied perspective. The background knowledge will provide a definite base in flourishing of the rehabilitation research 16. As it is so difficult to erase the rehabilitation research barriers, we must work coherently to minimize such limitations, as much as we can, to enhance the quality of the work we produce in contributing towards the growing domain of rehabilitation. Creating awareness among the people about destigmatizing the participation in research, awareness among the users, customizing the users’ interface and providing proper training to the students/researchers 17 helps positively in potentiating the achievement of required goals of rehabilitation research. Training of library professionals 18 to assimilate digital competencies in developing, managing and protecting digital libraries and their contents 11, proper administrative, mentoring and financial support will also contribute in enhancing the rehabilitation research.